17.1% Efficient Single‐Junction Organic Solar Cells Enabled by n‐Type Doping of the Bulk‐Heterojunction. Issue 7 (13th February 2020) - Lin, Yuanbao; Firdaus, Yuliar; Nugraha, Mohamad Insan; Liu, Feng; Karuthedath, Safakath; Emwas, Abdul‐Hamid; Zhang, Weimin; Seitkhan, Akmaral; Neophytou, Marios; Faber, Hendrik; Yengel, Emre; McCulloch, Iain; et al.
Abstract: Molecular doping is often used in organic semiconductors to tune their (opto)electronic properties. Despite its versatility, however, its application in organic photovoltaics (OPVs) remains limited and restricted to p‐type dopants. In an effort to control the charge transport within the bulk‐heterojunction (BHJ) of OPVs, the n‐type dopant benzyl viologen (BV) is incorporated in a BHJ composed of the donor polymer PM6 and the small‐molecule acceptor IT‐4F. The power conversion efficiency (PCE) of the cells is found to increase from 13.2% to 14.4% upon addition of 0.004 wt% BV. Analysis of the photoactive materials and devices reveals that BV acts simultaneously as n‐type dopant and microstructure modifier for the BHJ. Under optimal BV concentrations, these synergistic effects result in balanced hole and electron mobilities, higher absorption coefficients and increased charge‐carrier density within the BHJ, while significantly extending the cells' shelf‐lifetime. The n‐type doping strategy is applied to five additional BHJ systems, for which similarly remarkable performance improvements are obtained. OPVs of particular interest are based on the ternary PM6:Y6:PC71 BM:BV(0.004 wt%) blend for which a maximum PCE of 17.1%, is obtained. The effectiveness of the n‐doping strategy highlights electron transport in NFA‐based OPVs as being a key issue. Abstract : Addition of the n‐type dopant benzyl viologen (BV) into several best‐in‐class organic bulk‐heterojunctions (BHJ) is shown to consistently improve the power conversion efficiency (PCE) of the resulting solar cells. The presence of BV inside the BHJs increases the absorption coefficient, balances charge transport, and enhances the charge‐carrier density. These synergistic effects result in organic photovoltaics with a maximum PCE of 17.1%.